ACIDFORM inactivates herpes simplex virus and prevents genital herpes in a mouse model: Optimal candidate for microbicide combinations - Tuyama, Ana C. G. (2006)
The acidic vaginal milieu is presumed to inactivate pathogens but is neutralized by semen. This notion fostered the development of acid-buffering products, such as ACIDFORM (developed by Program for Topical Prevention of Conception and Disease, Rush University, and licensed by Instead), as microbicides. However, the extent and mechanism of protective activity provided by buffering gels is not known. Exposure of herpes simplex virus (HSV) to pH 4.5 or lower irreversibly inactivated HSV and reduced HSV yields by at least 90%; exposure to pH 5.0 had little or no effect. Pretreatment of HSV-2 with pH 3.5-4.5 triggered proteolysis, disrupting the HSV particle and resulting in a reduction in binding and invasion. ACIDFORM protected 21 (81%) of 26 mice from genital herpes, compared with 3 (12%) of 25 mice who received a placebo gel. ACIDFORM retained significant activity if mice were challenged with HSV delivered in seminal fluid. These findings suggest that ACIDFORM offers considerable protection against HSV and may be an optimal candidate for developing combination microbicides.